Serum-based microRNA signatures in early diagnosis and prognosis prediction of colon cancer. (1st August 2016) - Vychytilova-Faltejskova, Petra; Radova, Lenka; Sachlova, Milana; Kosarova, Zdenka; Slaba, Katerina; Fabian, Pavel; Grolich, Tomas; Prochazka, Vladimir; Kala, Zdenek; Svoboda, Marek; Kiss, Igor; Vyzula, Rostislav; et al.
Summary: A serum-based panel comprising of four miRNAs was established enabling early detection of colon cancer. Further, the prognostic model based on the expression of two miRNAs independent of TNM stage was developed. Abstract : Early detection of colorectal cancer is the main prerequisite for successful treatment and reduction of mortality. Circulating microRNAs were previously identified as promising diagnostic, prognostic and predictive biomarkers. The purpose of this study was to identify serum microRNAs enabling early diagnosis and prognosis prediction of colon cancer. In total, serum samples from 427 colon cancer patients and 276 healthy donors were included in three-phase biomarker study. Large-scale microRNA expression profiling was performed using Illumina small RNA sequencing. Diagnostic and prognostic potential of identified microRNAs was validated on independent training and validation sets of samples using RT-qPCR. Fifty-four microRNAs were found to be significantly deregulated in serum of colon cancer patients compared to healthy donors ( P < 0.01). A diagnostic four-microRNA signature consisting of miR-23a-3p, miR-27a-3p, miR-142-5p and miR-376c-3p was established (AUC = 0.917), distinguishing colon cancer patients from healthy donors with sensitivity of 89% and specificity of 81% (AUC = 0.922). This panel of microRNAs exhibited high diagnostic performance also when analyzed separately in colon cancer patients in early stages of the disease (T1-4N0M0; AUC = 0.877). Further, a prognostic panel based on the expression of miR-23a-3p and miR-376c-3p independent of TNM stage was established (HR 2.30; 95% CI 1.44–3.66; P < 0.0004). In summary, highly sensitive signatures of circulating microRNAs enabling non-invasive early detection and prognosis prediction of colon cancer were identified.